2011
DOI: 10.1038/nrmicro2505
|View full text |Cite
|
Sign up to set email alerts
|

Signal processing in complex chemotaxis pathways

Abstract: Bacteria use chemotaxis to migrate towards environments that are better for growth. Chemoreceptors detect changes in attractant levels and signal through two-component systems to control swimming direction. This basic pathway is conserved across all chemotactic bacteria and archaea; however, recent work combining systems biology and genome sequencing has started to elucidate the additional complexity of the process in many bacterial species. This article focuses on one of the best understood complex networks, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
344
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 401 publications
(350 citation statements)
references
References 135 publications
4
344
0
2
Order By: Relevance
“…2). This is likely the reason that even the few bifunctional HKs that have more than one target rarely act on more than two or three downstream RRs (34,38). Monofunctional HKs, however, should act more like kinases in GK loops (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). This is likely the reason that even the few bifunctional HKs that have more than one target rarely act on more than two or three downstream RRs (34,38). Monofunctional HKs, however, should act more like kinases in GK loops (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there are known examples of HKs that act efficiently on more than one RR (e.g., the bacterial chemotaxis pathway) (38). Although introducing crosstalk does decrease response, the system can compensate by increasing the total expression level of that particular RR to maintain a particular concentration of active RR* (SI Appendix) (3).…”
Section: Discussionmentioning
confidence: 99%
“…2A). Classic chemotaxis systems use CheY as the response regulator downstream of CheA (18). The Chp system has two apparent CheY homologs, PilG and PilH, which have opposite effects on cAMP levels (9).…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the M. gryphiswaldense genome for genes that might encode proteins involved in aerotaxis revealed at least 56 genes encoding putative chemoreceptors 20 , known as methyl-accepting chemotaxis proteins (MCPs) (Supplementary Table 3), and four putative chemotaxis operons designated cheOp1-4 (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
“…Chemotactic signal transduction in all bacteria is based on two-component systems involving autophosphorylation of the histidine kinase, CheA, followed by subsequent phosphotransfer to a response regulator, CheY 20 . We found that of the ARTICLE four identified chemotaxis operons of M. gryphiswaldense, only cheOp1, comprising the canonical set of chemotaxis genes (cheAWYBR), is involved in aerotaxis and swimming polarity (Fig.…”
Section: Discussionmentioning
confidence: 99%